The Association of Non-Conformance Toward Unsafe Act and Condition in Mills PT XYZ: The Correlational Study - Muhammad Isranul Hakim; Perie Anugraha Wiguna; Elen Sahan Wijaya; Robi Kurnia (GLOBAL HEALTH SCIENCE GROUP, 2025)
The issue of workplace safety is a critical concern globally, particularly in high-risk industries such as manufacturing and milling. Using quantitative methods. This study aims to investigate the relationship between non-compliance with safety protocols and the prevalence of unsafe acts and conditions across 37 mills at PT XYZ, which includes 14 paper buyer mills, 13 paper pulp mills, and 10 paper tissue mills. We collected data in May from secondary sources such as safety records and incident reports and then used the Statistical Package for the Social Sciences (SPSS) for analysis. We performed normality tests prior to conducting correlation analyses to ensure the appropriateness of the applied statistical methods. The study of Mill PT XYZ (N=37) found weak negative correlations between non-conformance and unsafe conditions (-0.292, p=0.80) and unsafe acts (0.140, p=0.410). This means that non-conformance does not have a big effect on unsafe behaviors. In the Paper Buyer Mills (N=14), correlations are weakly positive for unsafe conditions (0.127, p=0.666) and weakly negative for unsafe acts (-0.402, p=0.154), both lacking significance. For the Paper Pulp Mills (N=13), weak negative correlations of -0.366 (p=0.219) and -0.455 (p=0.118) also show no significance. The Paper Tissue Mills (N=10) have a moderately negative correlation of -0.599 (p=0.067), which points to a possible link between higher non-conformance and unsafe conditions. However, the correlation with unsafe acts (0.238, p=0.508) is still weak, which makes it challenging to draw firm conclusions.